High performance IGZO/TiO2 thin film transistors using Y2O3 buffer layers on polycarbonate substrate - Hsu, H. H.; Chang, C. Y.; Cheng, C. H. (My University, 2013)
In this work, we fabricate IGZO TFT devices on flexible substrate at room temperature. The IGZO/TiO2 TFT has small subthreshold swing of 0.16 V/dec, but suffers large gate leakage and negative threshold voltage. However, the TiO2 TFT with Y2O3 buffer layers shows improved characteristics including a low threshold voltage of 0.55 V, a small sub-threshold swing of 0.175 V/decade and high field-effect mobility of 43 cm(2)/Vs. Such good performance can be attributed to the enhanced capacitance density and lowered gate leakage owing to the integration of large band gap Y2O3 and low-temperature higher-kappa TiO2.